Contextual Chemistry and Physics Teaching in an Undergraduate Nanotechnology Degree - Richmond, William (International Council on Materials Education, 2008)
Curtin University established a Bachelor of Science (Nanotechnology) degree in 2002 as a jointprogram between the departments of Applied Chemistry and Applied Physics. This paper describesthe structure of the degree and the approaches taken in the development of a stream ofnanotechnology units aimed at enhancing the teaching of fundamental concepts in Physics andChemistry within a Nanotechnology context. Student perceptions of the value of thesenanotechnology units are also discussed.